Effects of SARS-CoV-2 pandemic confinement on metabolic disorders (obesity and DM2) and breast lobular carcinoma - Bello Torres, Jimmy Harvey; Benítez Medina, Laura Ginet (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
The isolation and confinement measures due to the SARS-Cov-2 pandemic had an impact on the treatment, monitoring and control of non-communicable diseases such as diabetes, breast lobular carcinoma and obesity according to the World Health Organization (WHO). Likewise, the imposition of strict measures by government agencies in many countries, including Colombia, to control and mitigate the outbreak of COVID-19, such as the closure of gyms, sports centers, and public spaces, led to a 35% decrease in the levels of physical activity at the beginning of this pandemic, which is a key point to analyze and propose strategies for the prevention of most chronic diseases.